The Diverse use of Clouds by CMS. Issue 2 (December 2015) - Andronis, Anastasios; Bauer, Daniela; Chaze, Olivier; Colling, David; Dobson, Marc; Fayer, Simon; Girone, Maria; Grandi, Claudio; Huffman, Adam; Hufnagel, Dirk; Khan, Farrukh Aftab; Lahiff, Andrew; et al.
Abstract: The resources CMS is using are increasingly being offered as clouds. In Run 2 of the LHC the majority of CMS CERN resources, both in Meyrin and at the Wigner Computing Centre, will be presented as cloud resources on which CMS will have to build its own infrastructure. This infrastructure will need to run all of the CMS workflows including: Tier 0, production and user analysis. In addition, the CMS High Level Trigger will provide a compute resource comparable in scale to the total offered by the CMS Tier 1 sites, when it is not running as part of the trigger system. During these periods a cloud infrastructure will be overlaid on this resource, making it accessible for general CMS use. Finally, CMS is starting to utilise cloud resources being offered by individual institutes and is gaining experience to facilitate the use of opportunistically available cloud resources. We present a snap shot of this infrastructure and its operation at the time of the CHEP2015 conference.